Phytochemistry and Pharmacology of Munronia Genus (Meliaceae) - Kindi Farabi; Unang Supratman (Universitas Gadjah Mada, 2021)
Munronia is a genus in the Meliaceae family, which consists of over 17 species that are distributed in the subtropical and tropical area of Asia, including southern China, Vietnam, Myanmar, Sri Lanka, India, Indonesia, and the Philippines. It is known that these plants contain valuable bioactive compounds. Since the first isolation of new stigmastane steroid was reported in 2003, researchers have been able to study the chemical composition of these plants, especially the largest secondary metabolite obtained, limonoid. About 97 compounds were isolated successfully and characterized. The reported compounds showed various biological activities, such as antifeedant, antimicrobial, antiangiogenic, cytotoxic against several cancer cell lines, inducing apoptosis, and anti-tobacco mosaic virus activities. Therefore, the results suggest that the use of this plant as a source of bioactive compounds is promising for the medicinal chemistry field.